Feasibility of SMS booster for alcohol reduction in injury patients in Tanzania. - Catherine A Staton; Mary Catherine Minnig; Ashley J Phillips; Arthi S Kozhumam; Msafiri Pesambili; Brian Suffoletto; Blandina T Mmbaga; Kennedy Ngowi; Joao Ricardo Nickenig Vissoci (PLOS Global Public Health, 2022)
Alcohol use is associated with 3 million annual deaths globally. Harmful alcohol use, which is associated with a high burden of disease in low- and middle-income countries (LMICs), often increases the probability of traumatic injury. Treatments for harmful alcohol use in LMICs, such as Tanzania, lack trained personnel and adequate infrastructure. The aim of this study was to assess the feasibility of using SMS boosters to augment a hospital based brief negotiational intervention (BNI) in this low resourced setting. We conducted a three stage, four arm feasibility trial of a culturally adapted BNI for injury patients with harmful and hazardous drinking admitted to Kilimanjaro Christian Medical Centre (KCMC) in Moshi, Tanzania. Post hospital discharge, two of the four arms included patients receiving either a standard or personalized short message service (SMS) booster to enhance and or perpetuate the effect of the in-hospital BNI. Text messages were sent weekly throughout a 3-month follow-up period. SMS feasibility was assessed according to the TIDier checklist evaluating what, when, how much, tailoring processes, modifications and how well (intervention fidelity). Data was collected with SMS logs and short answer surveys to participants. A total of 41 study participants were assigned to each receive 12 SMS over a three-month period; 38 received messages correctly, 3 did not receive intended messages, and 1 received a message who was not intended to. Of the 258 attempted texts, 73% were successfully sent through the messaging system. Of the messages that failed delivery, the majority were not able to be sent due to participants traveling out of cellular service range or turning off their phones. Participants interviewed in both booster arms reported that messages were appropriate, and that they would appreciate the continuation of such reminders. At 6-month follow-up, 100% (n = 11) of participants interviewed believed that the boosters had a positive impact on their behavior, with 90% reporting a large impact. This study demonstrated feasibility and acceptability of the integration of SMS mobile health technology to supplement this type of nurse-led BNI. SMS booster is a practical tool that can potentially prolong the impact of a brief hospital based intervention to enact behavioral change in injury patients with AUD.